Work and Citizenship in Mexico in the Era of Globalization - García, Arnulfo (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2005)
This article analyzes the case of Mexico in order to provide an overview of citizenship at work in the context of a dependent regional economy in a global era. It examines the framework of rights (civil, political and social) linked to the condition of the working class in a state-corporatist labour regulation model. It also explores the repercussions for workers, both at work and beyond the workplace, of current transitions from this model as well as looking at the redefinition of labour rights now taking place. Four different segments of the labour force are used to illustrate the nature of the historical and continuing deficit in the exercise of citizenship at work. This preliminary exploration leads to the identification of some paths for future research.